2008
DOI: 10.1159/000167799
|View full text |Cite
|
Sign up to set email alerts
|

Hyperinsulinemia and Insulin Resistance, Early Cardiovascular Risk Factors in Children with Chronic Kidney Disease

Abstract: Background/Aims: Pediatric chronic kidney disease (CKD) is associated with increased risk of cardiovascular disease. Still, hyperinsulinemia and insulin resistance, common cardiovascular risk factors, are not extensively investigated in children with CKD. We hypothesize that insulin abnormalities are present also in pediatric mild to moderate CKD, and associated with inflammation and malnutrition. Methods: We enrolled 26 children with CKD, and 34 healthy controls for analyses of blood samples and body composit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 80 publications
0
4
0
Order By: Relevance
“…Circulating levels of insulin keep an inverse relationship with those of IGFBP-1 and IGFBP-2 in children with nutritional disorders (22,23). Thus, the association of high concentrations of IGFBP-1 and IGFBP-2 with normal values of serum insulin suggests that the status of insulin resistance reported in children with CRF (24,25) is present in well-nourished infants with CRF and is not modified by GH therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Circulating levels of insulin keep an inverse relationship with those of IGFBP-1 and IGFBP-2 in children with nutritional disorders (22,23). Thus, the association of high concentrations of IGFBP-1 and IGFBP-2 with normal values of serum insulin suggests that the status of insulin resistance reported in children with CRF (24,25) is present in well-nourished infants with CRF and is not modified by GH therapy.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it was shown that short-term aerobic exercise improved stiffness index ␤ at least in part via increasing insulin sensitivity [31] . Insulin resistance develops inevitably in patients who have impaired renal function [32] , and a high prevalence of IR has been found in ESRD [33][34][35] . The gold standard method for IR is euglycemic glucose clamp technique, which is far too labor intensive.…”
Section: Discussionmentioning
confidence: 99%
“…IR is present in patients with early CKD and progressively worsens as the disease progresses to end-stage renal disease. IR may participate in the occurrence and development of CKD through such mechanisms as a hyperinsulinemic reaction ( 14 ), induction of oxidative stress ( 15 ), activation of a sympathetic renin-angiotensin-aldosterone system ( 16 ), activation of inflammatory factors ( 17 ), and inhibition of insulin signaling pathway ( 18 ). Cheng HT al ( 19 ).…”
Section: Discussionmentioning
confidence: 99%